Dependence of thermoelectric power and electrical conductivity on structural order of PEDOT-Tos-graphene nanocomposite via charge carrier mobility. (18th September 2019) - Maity, Shilpa; Kulsi, Chiranjit; Banerjee, Shiladitya; Das, Sukhen; Chatterjee, Krishanu
Abstract: Nanocomposites of tosylate doped poly (3, 4 ethylenedioxythiophene) (PEDOT-Tos) and graphene with improved structural order were synthesized and investigated as organic thermoelectric (TE) materials. A TE figure of merit ZT > 0.05 is reported. Gradual incorporation of graphene results in an increase in the degree of structural order of the samples. A consequent increase in the figure of merit is observed, the maximum value crossing 0.05 (higher than that reported for bulk nanostructured polymer based composites) for a graphene content of 25%. The tuning of the ordered structure boosts up the charge carrier mobility, which in turn improves the thermoelectric power (S) simultaneously with the electrical conductivity ( σ ). Consequently there is an increase in the TE power factor. Moreover, the thermal conductivity of the nanocomposites is very low due to selective phonon scattering by the introduction of the nanointerfaces designed in the PEDOT-Tos-graphene nanocomposites, which further contributes to the enhancement in ZT. An opposite trend is observed in structure and ZT, for a graphene content of 40%; arising probably from reduced π -stacking interactions between graphene and the PEDOT units. This study proves to be an effective way and can escort the future design and synthesis of high-performance thermoelectric conjugated polymers.